Antiracism in the LIS Profession: Not Just Lip Service. Issue 1 (13th October 2021) - Tang, Rong; Goodman, Xan; Davis, Rebecca; Du, Jia Tina; Pride, Bridgett; Leonard, David
Abstract: With rising cases of brutality, gun violence, and racial injustice towards particularly the Black and AAPI (Asians, Asian Americans, Pacific Islanders) communities, racism is being recognized and declared as an emergency and public health threat. Diversity, equity, and antiracism are core to the Library and Information Science (LIS) profession as we strive to uphold the principle of "libraries serve humanities" and the motto of "free to all." During this extended period of "racial‐injustice as a public crisis", what are the roles of LIS professionals in battling racism, violence, and other systems of oppression? This panel session features experienced LIS professionals and educators who specialize in DEI, reporting their activities, stories, and thoughts on antiracism. A breakout room activity is envisioned following panelists' presentations, with participants discussing and sharing their antiracism initiatives. Participants will also brainstorm the next course of action in the LIS profession's journey in battling racism.